Oxygen Anion Redox Chemistry Correlated with Spin State in Ni‐Rich Layered Cathodes. Issue 9 (25th January 2023) - Lu, Zhihua; Zhang, Jicheng; Zhang, Qinghua; Wong, Deniz; Yin, Wen; Zhang, Nian; Chen, Zhongjun; Gu, Lin; Hu, Zhongbo; Liu, Xiangfeng
Abstract: Despite the low cost and high capacity of Ni‐rich layered oxides (NRLOs), their widespread implementation in electric vehicles is hindered by capacity decay and O release. These issues originate from chemo‐mechanical heterogeneity, which is mainly related to oxygen anion redox (OAR). However, what to tune regarding OAR in NRLOs and how to tune it remains unknown. In this study, a close correlation between the OAR chemistry and Li/Ni antisite defects is revealed. Experiments and calculations show the opposite effects of aggregative and dispersive Li/Ni antisite defects on the NiO6 configuration and Ni spin state in NRLOs. The resulting broad or narrow spans for the energy bands caused by spin states lead to different OAR chemistries. By tuning the Li/Ni antisite defects to be dispersive rather than aggregative, the threshold voltage for triggering OAR is obviously elevated, and the generation of bulk‐O2 ‐like species and O2 release at phase transition nodes is fundamentally restrained. The OAR is regulated from irreversible to reversible, fundamentally addressing structural degradation and heterogeneity. This study reveals the interaction of the Li/Ni antisite defect/OAR chemistry/chemo‐mechanical heterogeneity and presents some insights into the design of high‐performance NRLO cathodes. Abstract : The aspects of oxygen anion redox (OAR) that should be tuned in Ni‐rich cathodes for improved performance and means of doing so is not clearly elucidated. Herein, a basic factor of spin state that influences OAR is discovered. Distinct spin states result from aggregative and dispersive Li/Ni disorder. The mechanism of spin states in tuning OAR chemistry is revealed.